A Study of American Education Issues Reflected by the Movie “Waiting for Superman” - Fuad Hasyim; Wajiran Wajiran (Journal of English Language and Education, 2022)
This article examines education issues in a documentary movie entitled “Waiting for Superman.” To do this research, the author applied the literary research method to find words, phrases, sentences, and scenes that explore the education problems in America. Meanwhile, the sociology of literature was employed to understand the social background and context of a particular story. The research found four issues in the movie: public education spending, students’ literacy level, conflicting regulations, and teacher unions. This research has contributed to American Studies by understanding the fundamental problem of American people in education. It has also taught educational stakeholders how to maintain a high-quality learning activity.